2010
DOI: 10.5005/jp-journals-10005-1049
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Antimicrobial Efficacy of MTAD, 3% NaOCl and Propolis Against E Faecalis

Abstract: AimThe present study sought to compare the antimicrobial efficacy of 3% NaOCl, Biopure MTAD (Tulsa Dentsply, Tulsa, OK) and Brazilian ethanolic extract of propolis (EEP) against Enterococcus faecalis (E. faecalis).MethodologyThe study utilized 55 extracted human permanent teeth with single root canal. The samples were decoronated, instrumented and sterilized. The teeth were infected with E faecalis for 48 hours. The teeth were divided randomly into 3 groups according to the irrigants used and kept in contact w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…18 It has been proved to be a less irritating solution 19 and were effective in eliminating Enterococcus faecalis. 20 21 Propolis was also found to induce the production of high-quality tubular dentin. 22 Propolis has been known to be a potent sensi-tizer, is allergenic, and may lead to eczematous contact dermatitis in some cases.…”
Section: Discussionmentioning
confidence: 96%
“…18 It has been proved to be a less irritating solution 19 and were effective in eliminating Enterococcus faecalis. 20 21 Propolis was also found to induce the production of high-quality tubular dentin. 22 Propolis has been known to be a potent sensi-tizer, is allergenic, and may lead to eczematous contact dermatitis in some cases.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, propolis showed less bacterial reduction effect than NaOCl, which is in accordance with Asha Nara study. (28) On the other hand, Al-Qathmi and Al-Madi (29) suggested that propolis root canal irrigant was as effective as NaOCl Sample no.…”
Section: Discussionmentioning
confidence: 99%
“…Although herbal intracanal irrigants have been used in permanent teeth, studies are limited in primary teeth. 16 17 Triphala solution in 10% Dimethyl sulfioxide (DMSO) has good antibacterial effect and can be used as an intracanal irrigant in permanent teeth. 6 No literature is available on the use of triphala in primary teeth.…”
Section: Discussionmentioning
confidence: 99%